A modification method of a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies

CN122934962APending Publication Date: 2026-10-16YUNNAN HUAPU QUANTUM MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610841956.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

金属功函数匹配法,通过选择高功函数金属(如Pt、Ni)以提升势垒高度,但该方法受限于金属材料种类的有限性以及界面缺陷态的不可控影响,难以实现势垒的精准、连续调控

Benefits of technology

1、本申请摒弃了传统依赖金属材料更换或高温掺杂的静态势垒调控思路,创新地采用超快激光对非晶氧化镓薄膜进行局部辐照处理;通过精确控制激光的能量密度、扫描间距和扫描速度等参数,能够定量、可控地在氧化镓薄膜表面引入氧空位缺陷;实验数据表明,随着激光处理能量的增加,氧空位浓度可从23.18%逐步提升至41.57%。氧空位浓度的增加导致薄膜内部电子浓度上升,费米能级上移,从而有效降低了ITO电极与氧化镓之间的截面势垒高度;本申请能够实现从高势垒肖特基接触到低势垒欧姆接触,乃至准欧姆接触的连续、动态过渡,解决了现有技术难以精准调控势垒高度的难题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122934962A_ABST
    Figure CN122934962A_ABST
Patent Text Reader

Abstract

The application discloses a modification method of a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies, and belongs to the technical field of photodetectors. The method comprises the following steps: depositing an amorphous gallium oxide film on an FTO substrate; using a laser light source, performing line scanning irradiation on the surface of the film through objective focusing, introducing oxygen vacancies and reducing roughness; and depositing an ITO electrode to construct an ITO / Ga2O3 / FTO vertical structure photodetector. Laser processing increases the oxygen vacancy concentration of the film surface from 23.18% to 41.57%, which reduces the ITO / Ga2O3 interface barrier height, and causes the device to generate self-powered light response under zero bias. When the oxygen vacancy concentration is higher than 40%, the polarity of the photocurrent of the device under ultraviolet light irradiation in the solar blind band (200nm-280nm) is reversibly controlled. The application realizes quantitative introduction of oxygen vacancies and accurate adjustment of the barrier height by laser parameter control, and has the advantages of simple process, non-destructive modification, controllable polarity and self-powered response.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photodetector technology, specifically to a method for modifying gallium oxide photodetectors by inducing oxygen vacancies using ultrafast lasers, and the resulting solar-blind ultraviolet photodetector. Background Technology

[0002] Solar-blind ultraviolet photodetectors have significant application value in fields such as fire early warning, missile tracking, non-line-of-sight communication, and environmental monitoring. Their core working principle relies on high sensitivity to ultraviolet light in the solar-blind band (especially 240nm~280nm). This band is naturally shielded from solar interference by the strong absorption of the Earth's ozone layer, enabling the detector to achieve ultraviolet signal detection with extremely low background noise.

[0003] Among many semiconductor materials, gallium oxide (Ga2O3), an ultrawide bandgap semiconductor, is considered an ideal material for constructing high-performance solar-blind ultraviolet detectors due to its intrinsic solar-blind absorption characteristics (bandgap of about 4.9 eV), high breakdown field strength (about 8 MV / cm), and excellent chemical and thermal stability.

[0004] Currently, gallium oxide-based solar-blind detectors mostly employ a metal-semiconductor-metal (MSM) structure, and their performance is primarily limited by the Schottky barrier characteristics at the interface between the metal electrode and gallium oxide. The barrier height directly affects the device's dark current, photoresponse speed, and response speed: a higher barrier helps suppress dark current but may hinder the effective separation and transport of photogenerated carriers; conversely, a lower barrier, while beneficial for carrier transport, easily leads to increased dark current and degraded signal-to-noise ratio. Existing mainstream barrier manipulation techniques and their limitations include: The metal work function matching method increases the barrier height by selecting metals with high work functions (such as Pt and Ni). However, this method is limited by the limited types of metal materials and the uncontrollable influence of interface defect states, making it difficult to achieve precise and continuous control of the barrier.

[0005] Interface doping / annealing processes can change the doping concentration near the interface through ion implantation or high-temperature annealing, but they can easily introduce lattice damage or impurity scattering centers, leading to a decrease in carrier mobility. Furthermore, high-temperature processes may be incompatible with some substrate or device structures.

[0006] Surface functional layer modification involves depositing a supermode dielectric layer (such as Al2O3) at the interface to adjust band alignment, but this increases process complexity and may introduce additional interface state charges, affecting device stability.

[0007] Furthermore, existing technologies mostly focus on optimizing static potential barriers, lacking the ability to dynamically and precisely control them. Although recent studies have attempted to achieve non-volatile modulation of potential barriers by inducing interface band reconfiguration through external stimuli such as optical fields and electric fields, these methods typically rely on complex external field coupling structures or high-energy-consuming driving conditions, making it difficult to meet the application requirements of device miniaturization, low power consumption, and programmability.

[0008] Laser micro / nano fabrication technology has shown great potential in semiconductor interface engineering due to its advantages such as high spatial resolution, non-contact processing, and controllable thermal effects. However, how to use laser technology to perform controllable and non-destructive defect engineering on gallium oxide thin films, and further achieve precise modulation of the metal / gallium oxide interface barrier and controllable reversal of the detector's photoresponse polarity, remains a pressing technical problem to be solved. Summary of the Invention

[0009] The purpose of this invention is to address the aforementioned problems by providing a method for modifying gallium oxide photodetectors with ultrafast laser-induced oxygen vacancies. This method selectively processes the electrode-semiconductor interface by setting the laser energy density, scanning spacing, and scanning speed to achieve barrier height modulation and further realize the dynamic reversal of the polarity (anode / cathode dominant) of the self-driving current of the solar-blind ultraviolet detector.

[0010] The technical solution of the present invention is as follows: A method for modifying gallium oxide photodetectors with ultrafast laser-induced oxygen vacancies includes the following steps: An amorphous gallium oxide thin film was deposited on an FTO substrate by radio frequency magnetron sputtering; Using a laser source, the laser is focused through an objective lens to irradiate the surface of an amorphous gallium oxide thin film by laser scanning. Oxygen vacancies are introduced by multiple equally spaced scanning lines, which simultaneously reduces the roughness of the film. An ITO electrode is deposited on the surface of the treated amorphous gallium oxide thin film, which together with the FTO substrate forms an ITO / Ga2O3 / FTO vertical structure photodetector.

[0011] The above method provides a simple and repeatable process for modifying gallium oxide photodetectors. It only requires an additional laser scanning step after conventional magnetron sputtering, eliminating the need for complex multilayer film structures or high-temperature annealing processes, thus significantly simplifying the fabrication process. The external excitation method of laser processing provides a technological basis for subsequent dynamic control of the potential barrier, solving the problem of the lack of dynamic control capabilities in existing technologies.

[0012] Furthermore, the laser scanning irradiation increases the oxygen vacancy concentration on the surface of the amorphous gallium oxide film, causing the Fermi level to shift upward, thereby reducing the interface barrier height between ITO and amorphous gallium oxide, and enabling the prepared photodetector to generate a self-powered photocurrent under solar-blind ultraviolet irradiation.

[0013] The above method reveals the causal relationship between laser-induced oxygen vacancies and barrier reduction, providing a clear theoretical basis for precise barrier control and overcoming the "black box operation" limitation of the metal work function matching method. By reducing the barrier, the device achieves photocurrent response (self-powered) under zero bias conditions, solving the power consumption problem caused by the need for external bias in traditional detectors.

[0014] Furthermore, the laser scanning irradiation increased the oxygen vacancy defect concentration on the surface of the amorphous gallium oxide thin film from 23.18% to 41.57%. The oxygen vacancy concentration was obtained by X-ray photoelectron spectroscopy peak fitting, where the O1s spectrum was decomposed into OⅠ peaks corresponding to lattice oxygen and OⅡ peaks corresponding to oxygen vacancies, and the oxygen vacancy content was the ratio of the area of ​​the OⅡ peak to the total peak area.

[0015] The above method enables quantitative characterization of oxygen vacancy concentration, providing a measurable and verifiable technical standard for laser treatment effects and overcoming the limitation of traditional methods in accurately quantifying defect concentration. By adjusting laser parameters, the oxygen vacancy concentration can be continuously controlled within the range of 23.18% to 41.57%, providing a quantitative basis for precise and dynamic control of the barrier height.

[0016] Furthermore, when the laser scanning irradiation increases the oxygen vacancy concentration on the surface of the amorphous gallium oxide thin film to more than 40%, the width of the depletion layer on the FTO side decreases to the extent that a tunneling effect occurs. The photocurrent polarity of the prepared photodetector under 254nm solar-blind ultraviolet irradiation is reversed relative to the low oxygen vacancy concentration device, and the device generates a photocurrent response under zero bias conditions.

[0017] Using the above method, the controllable reversal of the photoresponse current polarity of a gallium oxide solar-blind ultraviolet detector was achieved for the first time. By controlling the laser energy, the device can be preset to exhibit anode- or cathode-dominated photoresponse characteristics. Under high oxygen vacancy concentration conditions, the device operates at zero bias voltage using the tunneling effect, achieving true self-powered solar-blind ultraviolet detection and significantly reducing power consumption.

[0018] Furthermore, the study also includes conducting solar-blind ultraviolet photoelectric response tests on the prepared photodetector. Specifically, the device is placed in an electromagnetically shielded dark box and connected to a semiconductor parameter analyzer via a probe station. The current-voltage characteristic curve is measured under no-light conditions. The device is irradiated with a solar-blind ultraviolet light source with a wavelength range of 200nm~280nm, and the response curve of photocurrent changing with time is measured. The polarity of photocurrent under different laser treatment conditions, as well as the photocurrent amplitude of the treated sample and the untreated sample, are recorded.

[0019] The above method provides a standardized performance evaluation approach, making device performance comparable under different laser processing conditions and facilitating process optimization and quality control. By recording the photocurrent polarity under different processing conditions, the polarity reversal effect can be visually verified, providing a reliable testing method for the fabrication of polarity-controllable detectors.

[0020] Furthermore, the parameters of the laser source are as follows: laser wavelength is 750nm~1064nm; frequency is above 500kHz, i.e., the frequency can be GHz; pulse width is picosecond to femtosecond level; laser power density range is 0.823mW~357.8mW; scanning spacing is 0.02mm~0.05mm; scanning speed is 20mm / s~50mm / s; single pulse energy range is 5.8nJ to 411.6nJ; by adjusting the laser output single pulse energy, the samples are defined as L1, L2, L3, L4, and L5 according to the increase of energy, corresponding to different degrees of modification; the laser is an ultrafast laser pulse, and its transient energy deposition suppresses the thermal diffusion effect, thereby avoiding damage to the amorphous gallium oxide lattice; laser scanning irradiation reduces the surface roughness of the amorphous gallium oxide film.

[0021] The above method provides a broad and continuous process window (a power density range of six orders of magnitude), allowing operators to select appropriate laser energy based on the target oxygen vacancy concentration for precise process control. The definition of the five-level energy gradient (L1-L5) provides an experimental framework for studying the quantitative relationship between oxygen vacancy concentration and device performance, facilitating the establishment of a complete mapping relationship between "process parameters → defect concentration → device performance".

[0022] Furthermore, the objective lens is a 100x objective lens, used to focus the laser onto the surface of the sample being processed; the degree of oxygen vacancy defect introduction is controlled by controlling the laser energy and scanning interval; the laser scanning irradiation adopts a multiple equal-interval scanning method, with a scanning interval of 20μm~50μm and a scanning speed of 20mm / s~50mm / s.

[0023] Using the above method, the high-magnification focusing of the 100x objective lens confines the laser energy within a micro-area. Combined with the scanning method, this achieves large-area uniform processing while avoiding thermal impact on non-irradiated areas, thus realizing selective and localized modification. Equally spaced scanning ensures the uniformity of the thin film surface treatment, avoiding inconsistent device performance caused by uneven processing.

[0024] Furthermore, the preparation parameters for the amorphous gallium oxide thin film are as follows: the target material is a Ga2O3 ceramic target with a purity ≥99%; the sputtering gas is high-purity argon gas with a flow rate of 20 sccm~40 sccm; the sputtering power is 80W~150W; the deposition time is 30 minutes~90 minutes; and the background vacuum degree of the sputtering chamber is 5×10⁻⁶. -4 The sputtering pressure is above Pa and is 1 Pa to 2 Pa. Before thin film deposition, the FTO substrate is ultrasonically cleaned with acetone, methanol and deionized water respectively, and then dried with high-purity nitrogen.

[0025] By optimizing magnetron sputtering parameters, high-quality initial amorphous gallium oxide films were obtained, providing a good substrate for subsequent laser processing and avoiding the need for additional post-processing due to poor film quality. Standardized substrate cleaning procedures ensured good adhesion between the film and the substrate, reducing the interference of interface impurities on device performance.

[0026] Furthermore, the ITO electrode is deposited by DC magnetron sputtering with a power of 80W~120W and a time of 10 minutes~30 minutes. The ITO electrode size is on the order of millimeters. The FTO substrate size is on the order of centimeters and the resistance value is 7Ω~15Ω. The fabricated photodetector has a vertical structure, in which the ITO electrode is located on top of the amorphous gallium oxide thin film and the FTO substrate serves as the bottom electrode.

[0027] Using the above method, a transparent conductive oxide ITO symmetrical to the bottom FTO is used as the top electrode, forming a symmetrical "metal oxide-semiconductor-metal oxide" structure, which is electrically equivalent to an MSM structure, simplifying the complexity of electrode design. The well-defined electrode dimensions and substrate specifications ensure the consistency of the device structure, facilitating subsequent testing and performance comparison.

[0028] Furthermore, the device used for laser line irradiation includes: a control center for setting laser energy, pulse width, and scanning path parameters; a pulsed laser with a wavelength of 1030 nm; a focusing optical system for focusing the laser beam onto the surface of the amorphous gallium oxide thin film; the device adjusts the laser output power by adjusting the magnitude of the input current, adjusts the sample irradiation wavelength and pulse width using modulation technology, and adjusts the laser energy using a combination of half-wave plate and polarizer or a continuous attenuator.

[0029] The complete device design, as described above, ensures the feasibility and repeatability of the technical solution, allowing others to build the same device to realize this application based on the description. Multiple energy adjustment methods (current adjustment, half-wave plate-polarizer, attenuator) provide flexible laser energy control, adapting to process scenarios with varying precision requirements.

[0030] Compared with existing technologies, the advantages of this invention are: 1. This application abandons the traditional static barrier control approach that relies on metal material replacement or high-temperature doping, and innovatively employs ultrafast laser to locally irradiate amorphous gallium oxide thin films. By precisely controlling parameters such as laser energy density, scanning spacing, and scanning speed, oxygen vacancy defects can be quantitatively and controllably introduced onto the surface of the gallium oxide thin film. Experimental data shows that as the laser treatment energy increases, the oxygen vacancy concentration can be gradually increased from 23.18% to 41.57%. The increase in oxygen vacancy concentration leads to an increase in the electron concentration inside the thin film and a shift in the Fermi level, thereby effectively reducing the cross-sectional barrier height between the ITO electrode and gallium oxide. This application can achieve a continuous and dynamic transition from high-barrier Schottky contacts to low-barrier ohmic contacts, and even quasi-ohmic contacts, solving the problem of precise barrier height control in existing technologies. 2. Based on precise control of the potential barrier, this application achieves controllable reversal of the photoresponse current polarity of a gallium oxide solar-blind ultraviolet detector. Experimental results show that with the increase of laser processing energy (i.e., the increase of oxygen vacancy concentration), the photocurrent of the device under 254nm solar-blind ultraviolet light irradiation not only increases significantly, but its polarity also undergoes a clear reversal. The device fabricated in this application can exhibit anode- or cathode-dominated photoresponse characteristics according to the pre-set laser processing conditions. Under high oxygen vacancy concentration conditions, the high concentration of electrons inside the device results in an extremely narrow depletion layer on the FTO side, generating a tunneling effect, which allows the device to operate without an external bias voltage (self-powered mode), realizing high-sensitivity self-powered solar-blind ultraviolet detection. This characteristic is significantly better than traditional detectors that rely on external bias voltage, meeting the application requirements of low-power, portable devices. 3. Compared with traditional methods such as ion implantation or high-temperature annealing, which are prone to introducing lattice damage or impurity scattering centers, the ultrafast laser (picosecond-level) processing used in this application has the characteristics of transient energy deposition; this process can limit the heat-affected zone to a very small area, effectively suppressing the thermal diffusion effect, and while controllably introducing surface oxygen vacancies, it avoids causing significant damage to the deep lattice of gallium oxide; laser processing can also reduce the surface roughness of the thin film; 4. The method of this application only requires adding laser scanning processing after conventional magnetron sputtering deposition of gallium oxide thin film to achieve in-depth optimization and control of device interface characteristics, without the need for complex multilayer film structures or high-temperature annealing processes; subsequent direct deposition of transparent top electrode (such as ITO) can obtain a vertical structure photodetector; the entire process is simple and comparable to standard semiconductors. 5. This application enables effective control of oxygen vacancy concentration and barrier height within a relatively wide process window by adjusting the laser energy density, scanning spacing, and scanning speed. This provides significant flexibility and technical reserves for the customized fabrication of gallium oxide solar-blind ultraviolet detectors for different application scenarios (such as those requiring high dark current suppression ratios or ultra-high photoresponsivity).

[0031] This application successfully solves several technical problems mentioned in the background art through an innovative method of ultrafast laser-induced oxygen vacancies, achieving precise, dynamic, and non-destructive control of the interface barrier of gallium oxide photodetectors. Based on this, a high-performance solar-blind ultraviolet detector with controllable polarity and self-powered characteristics is obtained, achieving significant technological progress. Attached Figure Description

[0032] Figure 1 This is a schematic diagram of a method for modifying gallium oxide photodetectors by inducing oxygen vacancies using ultrafast lasers.

[0033] Figure 2 This is a quantitative analysis diagram of the oxygen vacancy content generated by laser in Example 3 of this application.

[0034] Figure 3 These are schematic diagrams of the solid-state device structures involved in Embodiments 1-2 of this application.

[0035] Figure 4 This is a model diagram of the potential barrier change of the ITO / a-Ga2O3 / FTO device involved in this application as the oxygen vacancy concentration increases.

[0036] Figure 5 This is a photocurrent response curve of different modified samples in Example 2 of this application under 254 nm solar-blind ultraviolet light. Detailed Implementation

[0037] It should be noted that relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0038] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0039] Please see Figure 1-5 A method for modifying gallium oxide photodetectors with ultrafast laser-induced oxygen vacancies, such as... Figure 1 As shown, by adjusting the interface barrier height between the electrode and amorphous gallium oxide, the current polarity reversal characteristic of the solar-blind ultraviolet photodetector is achieved. This method utilizes laser-induced defect stages on the material surface to influence the electronic properties of the material, thereby improving the performance of the solar-blind photodetector. Specifically, it includes the following steps: Preparation of amorphous gallium oxide thin films: Using transparent conductive materials such as FTO or ITO as substrates, before thin film deposition, the substrates are ultrasonically cleaned for 10-30 minutes each with acetone, methanol, and deionized water to remove surface impurities and organic matter. The substrates are then dried with high-purity nitrogen to obtain clean, dry substrates for later use. A high-purity Ga2O3 ceramic target with a purity greater than 99.99% is mounted on the magnetron sputtering cathode, and the cleaned FTO substrate is fixed on the sample stage. The sputtering chamber is evacuated to a vacuum, and high-purity argon gas is introduced as the sputtering gas. Pre-sputtering is performed before the actual sputtering to remove surface contaminants from the target and stabilize the sputtering conditions. The baffle is then opened, and the actual sputtering begins. After sputtering is complete, the sputtering system is shut off, and the substrate with the deposited amorphous gallium oxide thin film is removed.

[0040] FTO can be selected as the substrate, or other substrates can be selected based on cost, conductivity and other requirements.

[0041] Sputter chamber vacuum level selected: 5×10 -4 For the sputtering process, the argon flow rate is selected as 20 sccm~40 sccm, the sputtering pressure is 1 Pa~2 Pa, and the frequency is 90 W~150 W.

[0042] The deposition time for amorphous gallium oxide thin films is 30 min to 90 min.

[0043] Laser processing technology: Laser energy regulation: The laser output power is adjusted by regulating the input current through the laser's electronic control system. Laser wavelength and pulse width adjustment: The wavelength and pulse width of the sample irradiation are adjusted using modulation technology.

[0044] Laser energy adjustment can be achieved using a combination of half-wave plate and polarizer or a continuous attenuator.

[0045] The laser parameters were 11 ps, 1030 nm, 500 kHz, and 4 pulses. The sample was fixed on the sample stage, and the laser was focused onto the surface of the sample using a 100x objective lens. The laser was focused onto the surface of the sample using the objective lens. The pulsed energy was radiated throughout the sample, inducing the generation of surface defects in the gallium oxide thin film.

[0046] The microscope objective is 100x, and different energy levels and scanning intervals are used to further control the degree of defect introduction.

[0047] Depositing different electrodes: Gold and ITO targets were used to deposit electrodes onto the laser-treated sample via DC sputtering. The electrode size was controlled by covering the surface with a titanium mask of appropriate size. The electrode size was 1 mm × 1 mm.

[0048] Testing method: Test conditions: The electrical and photoelectric response characteristics of the devices were tested using a high-precision semiconductor parameter analyzer (Keithey 4200) connected to a probe station, and compared with untreated samples; changes in sample current characteristics under different laser treatment conditions were also observed. All electrical measurements were performed in an electromagnetically shielded dark chamber to eliminate ambient light interference and electromagnetic noise. Specific test items included: measuring the IV scan curve of the voltage under no-light conditions to evaluate the Schottky contact characteristics.

[0049] The optimal absorption wavelength for solar-blind ultraviolet light sources is 254 nm for Ga2O3.

[0050] Compared with the prior art, the advantages of this invention are: Existing technologies largely focus on optimizing static potential barriers, lacking exploration of dynamic barrier control capabilities. Recent research indicates that non-volatile modulation of barrier heights can be achieved by inducing interface band reconfiguration through external stimuli (such as optical or electric fields), thereby endowing detectors with programmable optoelectronic properties. However, such methods typically rely on complex external field coupling structures or high-energy-consumption driving conditions, making it difficult to meet the demands of miniaturized, low-power devices. Laser micro / nano fabrication technology, due to its advantages such as high spatial resolution (submicron level), non-contact processing, and controllable thermal effects, has demonstrated unique potential in semiconductor interface engineering. For example, femtosecond laser-induced localized thermal effects can precisely control the chemical composition and defect state distribution of metal-semiconductor interfaces, thereby altering Schottky barrier characteristics. Furthermore, transient energy deposition from ultrafast laser pulses (picosecond to femtosecond levels) can suppress thermal diffusion effects, avoiding damage to gallium oxide lattices. This characteristic provides a novel approach for developing new dynamic interface barrier control technologies.

[0051] The following will further illustrate this point with specific real-world examples: Example 1: FTO was selected as the substrate material, with dimensions of 20 mm × 10 mm × 1.1 mm and a resistivity of 7 Ω. The substrate was ultrasonically cleaned sequentially with ethanol, acetone, and deionized water for 10 min, followed by nitrogen gas to remove surface moisture and maintain dryness. It was then placed in an RF cavity, and an amorphous gallium oxide thin film was deposited using a gallium oxide target at 150 W for 60 min, resulting in an amorphous gallium oxide thin film.

[0052] Example 2: The prepared sample was placed on a stage, and the stage was adjusted to ensure that the sample surfaces were at the same height, and the laser focus was perpendicularly focused on the sample surface. An ultrafast high repetition rate infrared laser with 11 ps, 1.7 GHz, and a wavelength of 1030 nm was used. The scanning interval was fixed at 30 μm, the scanning speed at 50 mm / s, and the repetition rate at 500 kHz. Subsequently, the energy intensity of the laser deposition onto the sample was changed to modify the thin film. Two main methods were used for modification: one was to change the laser output single pulse energy (5.8, 47.2, 177.2, 246.8, 411.6 nJ) and define the samples as L1~L5 according to the energy increase. Electrode deposition was performed on the laser-treated sample, and the solar-blind ultraviolet detection response in the 254 nm wavelength range was tested with that of the untreated sample.

[0053] like Figure 5As shown, the time response curves (It) of samples L1~L5 under illumination on / off conditions are displayed. The figure clearly shows that with the increase of laser processing energy (i.e., the increase of oxygen vacancy concentration), the solar-blind ultraviolet photocurrent of the device is significantly increased and the current polarity changes, verifying the significant enhancement effect of laser modification on the self-powered detection performance.

[0054] Example 3: After laser scanning modification was completed in Example 2, samples with different modification levels (L1~L5) and untreated samples were selected for top electrode fabrication to complete the construction of the vertical photodetector: Masking: A customized stainless steel mask was used to cover the sample surface, exposing the laser scanning area (i.e., the active area). Top electrode deposition: Indium tin oxide thin film was deposited as the top electrode using DC magnetron sputtering at room temperature. In2O3:SnO2 (90:10 wt%) target was selected, sputtering power was 100W, and deposition time was 30min. Device forming: After fabrication, a vertical structure device with "top ITO / middle a-Ga2O3 / bottom FTO" was obtained (see Figure 3 The figure illustrates the layered structure of the device. From bottom to top, it consists of an FTO conductive glass substrate, an amorphous gallium oxide (a-Ga2O3) thin film layer modified by GHz laser scanning, and an ITO top electrode. The figure also illustrates the principle of the device's photoresponse current generation. Since both ITO and FTO are degenerate semiconductor metal oxides, this structure is electrically equivalent to a "metal-semiconductor-metal" (MSM) structure.

[0055] like Figure 2 As shown in the figure, this is an XPS peak fitting diagram of the O 1s core energy level for samples L1-L5 and the control group Ref. The figure displays three sub-peaks: the OI peak corresponding to lattice oxygen (approximately 530.6 eV) and the OII peak corresponding to oxygen vacancies (approximately 531.4 eV). By comparing the changes in the area ratio of the OII peak under different laser energies, the positive correlation between laser energy and induced oxygen vacancy concentration is quantitatively demonstrated.

[0056] like Figure 4 As shown, the process is divided into three stages. (a) Before processing: This demonstrates the high Schottky barrier at both ends of α-Ga2O3 in equilibrium. (b) Low-energy processing: This shows the Fermi level shifting upwards, the ITO-side barrier decreasing, and the device exhibiting unidirectional rectification characteristics. (c) High-energy processing: This shows the Fermi level pinned near the bottom of the conduction band. At this point, due to the extremely high electron concentration and the extremely narrow depletion layer on the FTO side, a tunneling effect occurs, and the device exhibits quasi-ohmic contact and self-powered photoresponse characteristics.

[0057] Example 4: This embodiment uses X-ray photoelectron spectroscopy (XPS) and microscopic mechanism analysis of samples before and after laser treatment to verify the introduction of oxygen vacancies and the improvement of surface morphology.

[0058] To quantitatively analyze the defect concentration variations in gallium oxide thin films, Gaussian-Lorentz peak fitting was performed on the XPS O1s core energy level spectrum. The O1s spectrum was decomposed into two main sub-peaks: OⅠ: located at a low binding energy (~530.8 eV), corresponding to lattice oxygen in the Ga-O bond; OⅡ: located at a high binding energy (~531.8 eV), corresponding to oxygen vacancies. Analysis of oxygen vacancy content in different samples: Table 1. Analysis of oxygen vacancy content in different samples Sample <![CDATA[Area O Ⅰ (CPS·eV)]]> <![CDATA[Area O Ⅱ (CPS·eV)]]> <![CDATA[O Ⅱ Ratio %]]> Unlaser 219580.69 66244.83 23.18% L1 103380.18 36740.60 26.22% L2 24862.29 16648.45 40.11% L3 84020.71 56345.27 40.14% L4 73756.34 52465.67 41.57% L5 92133.56 47594.38 34.06% The embodiments described above merely illustrate specific implementation methods of this application, and while the descriptions are detailed and specific, they should not be construed as limiting the scope of protection of this application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the technical solution of this application, and these modifications and improvements all fall within the scope of protection of this application.

Claims

1. A method for modifying gallium oxide photodetectors with ultrafast laser-induced oxygen vacancies, characterized in that, Includes the following steps: An amorphous gallium oxide thin film was deposited on an FTO substrate by radio frequency magnetron sputtering; Using a laser source, the laser is focused through an objective lens to irradiate the surface of an amorphous gallium oxide thin film by laser scanning. Oxygen vacancies are introduced by multiple equally spaced scanning lines, which simultaneously reduces the roughness of the film. An ITO electrode is deposited on the surface of the treated amorphous gallium oxide thin film, which together with the FTO substrate forms an ITO / Ga2O3 / FTO vertical structure photodetector.

2. The method for modifying a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies according to claim 1, characterized in that, The laser scanning irradiation increases the oxygen vacancy concentration on the surface of the amorphous gallium oxide film, causing the Fermi level to shift upward. This reduces the interfacial barrier height between ITO and amorphous gallium oxide, and enables the fabricated photodetector to generate a self-powered photocurrent under solar-blind ultraviolet irradiation.

3. The method for modifying a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies according to claim 1, characterized in that, The laser scanning irradiation increased the oxygen vacancy defect concentration on the surface of the amorphous gallium oxide thin film from 23.18% to 41.57%. The oxygen vacancy concentration was obtained by X-ray photoelectron spectroscopy peak fitting, where the O1s spectrum was decomposed into OⅠ peaks corresponding to lattice oxygen and OⅡ peaks corresponding to oxygen vacancies, and the oxygen vacancy content was the ratio of the area of ​​the OⅡ peak to the total peak area.

4. The method for modifying a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies according to claim 1, characterized in that, When the laser scanning irradiation increases the oxygen vacancy concentration on the surface of the amorphous gallium oxide thin film to more than 40%, the width of the depletion layer on the FTO side decreases to the extent that tunneling effect occurs. The photocurrent polarity of the prepared photodetector under 254nm solar-blind ultraviolet irradiation is reversed relative to the low oxygen vacancy concentration device, and the device generates photocurrent response under zero bias conditions.

5. The method for modifying a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies according to claim 1, characterized in that, The study also includes conducting solar-blind ultraviolet photoelectric response tests on the prepared photodetector. Specifically, the device is placed in an electromagnetically shielded dark box and connected to a semiconductor parameter analyzer via a probe station. The current-voltage characteristic curve is measured under no-light conditions. The device is irradiated with a solar-blind ultraviolet light source with a wavelength range of 200nm to 280nm, and the response curve of photocurrent over time is measured. The polarity of the photocurrent under different laser treatment conditions, as well as the photocurrent amplitude of the treated and untreated samples, are recorded.

6. The method for modifying a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies according to claim 1, characterized in that, The parameters of the laser source are as follows: laser wavelength is 750nm~1064nm, frequency is above 500kHz; pulse width is picosecond to femtosecond; laser power density range is 0.823mW~357.8mW; scanning spacing is 0.02mm~0.05mm; scanning speed is 20mm / s~50mm / s; single pulse energy range is 5.8nJ to 411.6nJ; by adjusting the laser output single pulse energy, the samples are defined as L1, L2, L3, L4, and L5 according to the increase of energy, corresponding to different degrees of modification; the laser is an ultrafast laser pulse, and its transient energy deposition suppresses the thermal diffusion effect, thereby avoiding damage to the amorphous gallium oxide lattice; laser scanning irradiation reduces the surface roughness of the amorphous gallium oxide film.

7. The method for modifying a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies according to claim 1, characterized in that, The objective lens is a 100x objective lens, used to focus the laser onto the surface of the sample being processed; the degree of oxygen vacancy defect introduction is controlled by controlling the laser energy and scanning interval; the laser scanning irradiation adopts a multiple equal-interval scanning method, with a scanning interval of 20μm~50μm and a scanning speed of 20mm / s~50mm / s.

8. The method for modifying a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies according to claim 1, characterized in that, The fabrication parameters for the amorphous gallium oxide thin film are as follows: the target material is a Ga2O3 ceramic target with a purity ≥99%; the sputtering gas is high-purity argon gas with a flow rate of 20 sccm~40 sccm; the sputtering power is 80W~150W; the deposition time is 30 minutes~90 minutes; and the background vacuum degree of the sputtering chamber is 5×10⁻⁶. -4 The sputtering pressure is above Pa and is 1 Pa to 2 Pa. Before thin film deposition, the FTO substrate is ultrasonically cleaned with acetone, methanol and deionized water respectively, and then dried with high-purity nitrogen.

9. The method for modifying a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies according to claim 1, characterized in that, The ITO electrode was deposited by DC magnetron sputtering with a power of 80W to 120W, a time of 10 minutes to 30 minutes, and a size of millimeters. The FTO substrate had a size of centimeters and a resistance of 7Ω to 15Ω. The fabricated photodetector had a vertical structure, with the ITO electrode located on top of the amorphous gallium oxide film and the FTO substrate serving as the bottom electrode.

10. The method for modifying a gallium oxide photodetector with ultrafast laser-induced oxygen vacancies according to claim 1, characterized in that, The device used for laser line irradiation includes: a control center for setting laser energy, pulse width, and scanning path parameters; a pulsed laser with a wavelength of 1030 nm; a focusing optical system for focusing the laser beam onto the surface of an amorphous gallium oxide thin film; the device adjusts the laser output power by adjusting the input current, uses modulation technology to adjust the sample irradiation wavelength and pulse width, and uses a combination of half-wave plate and polarizer or a continuous attenuator to adjust the laser energy.